Pharmaceutical packaging and ID cards with printed antennas of RFID tags - Kavčič, Urška; Đokić, Miloje; Maček, Marijan; Radonić, Vasa; Muck, Tadeja (Univerzita Pardubice, 2013)
The integration of RFID tags in different applications is important in order to gain greater functionality in products. Upon packaging, box tracking in logistics or in the supply chain can easily be achieved [1]. High manufacturing costs have led to the search for alternative manufacturing methods at an ultra-low cost and various printing processes have been considered such as inkjet, gravure, flexo, offset and screen printing. Currently, investigations are focused on the use of these printing technologies for the mass production of RFID directly on different printing materials such as papers, cardboards and foils [2–12]. This paper is an upgrade of our preliminary research [13] focused on antenna design and optimization of printing conditions. The analysis of the readability of UHF RFID tags, which were printed on real pharmaceutical packaging (of tablets) and on ID cards with printed and multi-layered laminated plastic cards were done. Two different antenna designs were printed. The first one on a packaging box and the second one on a foil layer which was then laminated with seven different foil layers. For printing thermal drying silver conductive printing ink was used. The NXP plastic strap chips were integrated with printed antennas using conductive glue. We found that printed antennas of UHF RFID tags and inline chip integration can swap the RFID tag label on packaging and RFID tag inlays in ID cards with printed ones. Preliminary results are promising, but to achieve better performance significant improvements have to be made in the near future.
Keywords: UHF RFID antenna; screen printing; packaging; ID cards